Filip Klega's Underground Collection? - Chrobák, Jakub (Bohemica Olomucensia, 2024)
The study analyses F. Klega's collection Andrstán in comparative relations not only to the Czech literary underground, but also asks to what extent the conceptual vocabulary that accompanies the collection, especially the notions of the Czech underground and "embarrassing poetry", is thought about in the texts that in some way reciprocate it. It also asks to what extent the freedom in the use of these terms is linked to the situation of literary criticism within the academically "measured" literary science.
Keywords: Literary scholarship; literary history; literary criticism; underground; "embarrassing poetry"